2008
DOI: 10.1021/ja8059039
|View full text |Cite
|
Sign up to set email alerts
|

Silica−Void−Gold Nanoparticles: Temporally Stable Surface-Enhanced Raman Scattering Substrates

Abstract: Reproducible detection of a target molecule is demonstrated using temporally stable solution-phase silica-void-gold nanoparticles and surface-enhanced Raman scattering (SERS). These composite nanostructures are homogeneous (diameter = 45 +/- 4 nm) and entrap single 13 nm gold nanoparticle cores inside porous silica membranes which prevent electromagnetic coupling and aggregation between adjacent nanoparticles. The optical properties of the gold nanoparticle cores and structural changes of the composite nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
213
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(221 citation statements)
references
References 45 publications
6
213
1
1
Order By: Relevance
“…230 By using this method, small bare gold nanoparticles can be encapsulated in the central cavity of hollowstructured silica nanoparticles. 203 On the other hand, some groups have reported that hollowstructured porous silica nanoparticles can be obtained without using stabilizers. Although the conversion process is quite slow, Zhang et al revealed that hollow-structured silica nanoparticles can be prepared successfully simply by immersing colloidal silica in a NaBH 4 solution without the involvement of PVP.…”
Section: Soft Template;mentioning
confidence: 99%
“…230 By using this method, small bare gold nanoparticles can be encapsulated in the central cavity of hollowstructured silica nanoparticles. 203 On the other hand, some groups have reported that hollowstructured porous silica nanoparticles can be obtained without using stabilizers. Although the conversion process is quite slow, Zhang et al revealed that hollow-structured silica nanoparticles can be prepared successfully simply by immersing colloidal silica in a NaBH 4 solution without the involvement of PVP.…”
Section: Soft Template;mentioning
confidence: 99%
“…Structures fabricated with multiple materials have been exploited to tune the plasmonic characteristics of the substrates to increase local electric field strengths or add functionality. These mixed material substrates include (i) dielectric materials coated with metals, [62][63][64]70 (ii) metals coated with dielectrics, 53,[71][72][73][74] (iii) semiconductors coated with metals, 75,76 and (iv) multilayered metal structures separated by dielectrics. 57,[77][78][79][80] One of the earliest and most prominent classes of these mixed material nanostructures for SERS sensing is known as core-shell nanoparticles, which consist of a dielectric core structure coated with a metallic shell [see Fig.…”
Section: Mixed Materialsmentioning
confidence: 99%
“…However, for the production of SERS labeled multifunctional nanomedicine, this sequence would induce problems because the pre-generated SERS disappeared because several severe synthesis conditions (high concentration of CTAB at the mSiO 2 coating process and NaOH etching stage) could detach Raman reporters from the metal substrates. Herein, we proposed a versatile "up-down" strategy, in which SERS nanosubstrates were pre-stabilized by polymers 32 or mesoporous materials, 33,34 followed by Raman reporters' subsequent mixing and infiltration step. In our case, it was crucial to load the Raman reporter DTDC and the therapeutic drug DOX at appropriate positions of the nanoplatform (on AuNR and in mTiO 2 , respectively), which determined the optical and therapeutic properties.…”
Section: Optical Characterization Of Aunr@void@mtio 2 Npsmentioning
confidence: 99%